Clinical Significance of Peripheral Blood T Lymphocyte Subsets in Helicobacter pylori-Infected Patients - Yuka Satoh; Hatsue Ogawara; Osamu Kawamura; Motoyasu Kusano; Hirokazu Murakami (Gastroenterology Research and Practice)
Background. Helicobacter pylori chronically colonizes gastric/duodenal mucosa and induces gastroduodenal disease and vigorous humoral and cellular immune responses. Methods. In order to clarify the immunological changes induced by this infection, we determined the percentage and, as indicated, ratios of the following cells in peripheral blood of 45 H. pylori-infected patients and 21 control subjects: CD4+ T cell, CD8+ T cells, T helper 1 cells (Th1), T helper 2 cells (Th2), CD4+CD25+ T cells, Foxp3+ regulatory T cells (Tregs), CD4/CD8 ratio, and Th1/Th2 ratio. Results. The percentage of CD8+ T cells was significantly lower in H. pylori-infected patients (mean±SD; 18.0±7.1%) compared to control subjects (mean±SD; 23.2±7.8%) (𝑃<0.05). The CD4/CD8 ratio was significantly higher in H. pylori-infected patients (mean±SD; 3.1±2.4) compared to control subjects (mean±SD; 2.1±1.0) (𝑃<0.05). The Th1/Th2 ratio was significantly lower in H. pylori-infected patients (mean±SD; 10.0±8.5) compared to control subjects (mean±SD; 14.5±9.0) (𝑃<0.05). The percentage of CD4+CD25+ T cells in H. pylori-infected patients (mean±SD; 13.2±6.2%) was significantly higher than that in control subjects (mean±SD; 9.8±3.4%) (𝑃<0.05). However, there was no significant difference in Tregs. Conclusion. Tregs did not decrease, but the activation of humoral immunity and Th2 polarization were observed in the peripheral blood of H. pylori-infected patients. In some cases, these changes may induce systemic autoimmune diseases.